2018
DOI: 10.1186/s40902-018-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Proportions of the aesthetic African-Caribbean face: idealized ratios, comparison with the golden proportion and perceptions of attractiveness

Abstract: BackgroundIn the absence of clear guidelines for facial aesthetic surgery, most surgeons rely on expert intuitive judgement when planning aesthetic and reconstructive surgery. One of the most famous theories regarding “ideal” facial proportions is that of the golden proportion. However, there are conflicting opinions as to whether it can be used to assess facial attractiveness. The aim of this investigation was to assess facial ratios of professional black models and to compare the ratios with the golden propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Of all the investigations, only 3 studies by Medici Filho et al, 27 Mizumoto et al, 29 and Garrido et al 32 are in accordance with Ricketts hypothesis. Other studies done by Moss et al, 24 Baker et al, 25 Shell et al, 26 Kiekens et al, 28 Pancherz et al, 30 Rossetti et al, 31 Siddik Malkoc and Fidancioglu, 33 Akan et al, 34 Mantelakis et al, 35 Burusapat and Lekdaeng 36 are in contrast with Ricketts hypothesis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Of all the investigations, only 3 studies by Medici Filho et al, 27 Mizumoto et al, 29 and Garrido et al 32 are in accordance with Ricketts hypothesis. Other studies done by Moss et al, 24 Baker et al, 25 Shell et al, 26 Kiekens et al, 28 Pancherz et al, 30 Rossetti et al, 31 Siddik Malkoc and Fidancioglu, 33 Akan et al, 34 Mantelakis et al, 35 Burusapat and Lekdaeng 36 are in contrast with Ricketts hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…Mantelakis et al 35 assessed the facial ratios of professional Black models using a Facial Ratio Calculator (The Accounting Resources Centre) and correlated the ratios with the golden proportion and concluded that no correlation was found between the facial ratios of the models and golden proportion. Burusapat and Lekdaeng 36 calculated the facial ratios of Miss Universe and Miss Universe Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Sforza et al described sex dimorphism, the inclination to average values, youthfulness and facial symmetry as four important criteria for ef icient treatment results (Sforza et al, 1994). Understanding and applying these indings to routine clinical practice can improve comprehension and provide with better quality results (Mantelakis et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The reverse applied is also true in most instances with the cephalometric method being applied accurately as well. The weak point of the photographic approach is its rather low sensitivity, meaning it might miss out on one out of two cases with actual growth pattern abnormality 14 .…”
Section: Resultsmentioning
confidence: 99%